The integration of foreign employees in the labour market - Heinz Werner (Intereconomics, 1996)
For a number of European countries the presence of a more or less large number of foreign workers and their families is a fact to which they will have to adjust. As a rule, the longer the length of their stay, the less probable it becomes that these workers will return to their country of origin. In view of this fact it is necessary that the foreign workers and their families are integrated as comprehensively as possible, for humanitarian, social and economic reasons. The following article examines a number of indicators for integration so far in France, Germany (West), the Netherlands and Sweden.
Keywords: 330